2018
DOI: 10.3329/bjm.v33i1.39602
|View full text |Cite
|
Sign up to set email alerts
|

Multi-drug resistant pathogenic Listeria monocytogenes in surface water and soil samples of Dhaka city

Abstract: Listeria monocytogenes, the causative agent of human listeriosis is widely distributed in nature and a major threat to human health. Aiming to investigate the environmental distribution of this pathogen in Bangladesh, the current study conducted an initial investigation on 30 soil samples and 20 surface water samples for the presence of the pathogenic Listeria monocytogenes. Based on cultural, morphological, biochemical tests and presence of the virulent gene hly, 7 (14%) Listeria monocytogenes were obtained o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 7 publications
1
5
2
Order By: Relevance
“…Contrary to our report, Manjur et al (2018) reported a high resistance of Lm from surface water in Bangladesh against ampicillin, trimethoprim-sulfamethoxazole, and penicillin and 100% resistance against erythromycin. A higher resistance against tetracycline (a class of oxytetracycline) was documented by Rodas-Suarez et al (2006).…”
Section: Rivercontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to our report, Manjur et al (2018) reported a high resistance of Lm from surface water in Bangladesh against ampicillin, trimethoprim-sulfamethoxazole, and penicillin and 100% resistance against erythromycin. A higher resistance against tetracycline (a class of oxytetracycline) was documented by Rodas-Suarez et al (2006).…”
Section: Rivercontrasting
confidence: 99%
“…Susceptibilities >50% were observed to other antibiotics tested ranging from 52.63% (cefotetan) to trimethoprim-sulfamethoxazole (98.25%) except for erythromycin (26.32%), sulfamethoxazole (35.09%), streptomycin (38.60%), oxytetracycline (45.61%), and amoxicillin (49.12%). Susceptibilities to imipenem and vancomycin in our study were lower compared to the report of Manjur et al (2018). Lm isolates showed varying percentages of resistance against all antibiotics tested except ampicillin for which no resistance was recorded similar to the report by Keet and Rip, (2021).…”
Section: Riversupporting
confidence: 49%
“…Furthermore, the bacterium has also been isolated from water samples collected from the point of sewage discharge (into a river) in Europe [ 53 ]. The study of Manjur et al [ 54 ] carried out in Bangladesh also investigated the distribution of Listeria spp. confirming the occurrence of the microorganisms in soil and surface water samples.…”
Section: Discussionmentioning
confidence: 99%
“…In Bangladesh, for instance, incidence rate of listeriosis is unknown and several factors can be attributed to it: lack of public awareness, overwhelmed medical sectors with other common diseases and underreporting of cases (Islam et al, 2016). Previously, there have been a few studies in Bangladesh addressing the incidence of Listeria in dairy food products and environment (Manjur et al, 2018), cattle farm environment (Shourav et al, 2020) and raw beef, chicken and chevon (Islam et al, 2016). To the best of our knowledge, this is the first study investigating the prevalence of multi-drug resistant pathogenic L. monocytogenes in RTE meat products in Bangladesh.…”
Section: Discussionmentioning
confidence: 99%